1852 Fla. Laws 137 - (:unkn) unknown (My University, 1852)
An Act To Prevent Fire Hunting in the County of St. Johns, ch. 558, § 1: Prohibited hunting by fire light in the night time with a gun or other firearms and not on one's own private property within the county of St. Johns. Violators fined not exceeding twenty-five dollars, or imprisoned not exceeding one month at discretion of the court.
Keywords: HUNTING REGULATION